Professionalization in Music through social projects: dialoguing with literature (Orfeu, 2024)
The aim of this paper is to reflect on the need for an expanded dialog with theorists from different fields of knowledge about how the concept of music profession is conceived. Based on the perspective of Music Education and the experience of the authors, the research also seeks to understand how the literature approaches professionalization in music based on social projects. Throughout the discussions, different professional spheres in which musicians work are interposed, with a view to elucidating how work in music is understood academically in Brazil and how the musician's profession is perceived within Music Education as an autonomous area of knowledge. The results also corroborate that social projects are crucial to promoting the training and professionalization in music of young people, especially those from marginalized communities, which in addition to training them in music promotes their integral formation and socio-professional insertion.
Keywords: musical education; social projects; training